Strategies to Improve Inadequate Bowel Preparation for Colonoscopy - Hernández, Goretti; Gimeno-García, Antonio Z.; Quintero, Enrique (Frontiers in Medicine, 2019)
Bowel cleansing is one of the most important parameters included in the evaluation of colonoscopy quality. The available evidence suggests that inadequate bowel preparation reduces the diagnostic yield of colorectal neoplasia and increases post-colonoscopy colorectal cancer risk. Nowadays, up to 30% of patients referred for colonoscopy have a poor bowel cleansing. Recently, several studies have analyzed the risk factors for inadequate bowel cleansing as well as the strategies to optimize bowel preparation. In this review, we have focused on summarizing the available evidence in this field.